Możliwości zwiększania zwrotności w badaniach ankietowych wśród przedsiębiorstw - Kaniewska-Sęba, Aleksandra; Leszczyński, Grzegorz (Possibilities of Increasing Manoeuvrability in Questionnaire Research among Companies, 2006)
The paper focuses on one aspect of postal and on-line surveys on business-to-business market - respondents' tendency to take part in it. The results of the presented research show that the response rate was higher in postal survey in comparison to on-line and fax ones. It is also shown how the research's subject, sponsor's kind, questionnaire length and the promise of sending survey results or an article affect the response rate.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 552-561